PENINGKATAN KETERAMPILAN MENULIS CERITA FABEL DENGAN MENGGUNAKAN MODEL PICTURE AND PICTURE DI KELAS VII SMP GLOBAL PRIMA NATIONAL PLUS SCHOOL TAHUN PELAJARAN 2018/2019 - Mesrani Nduru; Monika Magdalena Sinaga; Lidya Christmawanti Sinaga; Ermina Waruwu (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2019)
This study aims to determine the quality of the process, the quality of results and the improvement of learning to write fables using picture and picture learning model. The problem of the research arose when the researcher interviewed Indonesian teachers in class VII-A of the GLOBAL PRIMA NATIONAL PLUS SCHOOL Middle School that the student's learning outcomes were still low 75 and still not reached the minimum completeness criteria. To answer the problems of the research, researchers conducted research using picture and picture learning models in improving student writing learning. The researcher used an action classroom research approach and used data collection methods by means of observation and tests. The research instrument consists of guidelines for observing observations for both students and researchers and guidelines for evaluating student work in writing fable stories. The research subjects (respondents) were the GLOBAL PRIMA NATIONAL PLUS SCHOOL. The data were analyzed by qualitative descriptive analysis techniques and quantitative descriptive analysis. Based on the methodology of the research, result of the research were obtaineda) Cycle I (one) with classical completeness quality process 74.07%, quality of result 59.25% and the quality of researchers using 45% learning models, b) Cycle II (two) with quality process classical completeness 88.88%, quality of results 92.59% and the quality of researchers using the learning model to be 100%. There is an increase in learning, namely an increase in process and student learning outcomes from cycle I, 59.25% to cycle II being 92.59%, with a increase percentage of 33.34%. Therefore the model of picture and picture learning model can help improve the learning process so that learning objectives are maximized.